Tanggung Jawab Hukum Antara Stasiun Solo Radio 92.9 Fm Dengan Perusahaan Dalam Pemasangan Iklan - Warman, Aditya; , Nuswardhani, S.H, S.U (2016)
One of the advertising medium is radio, and therefore required good cooperation between producer and radio. Because the radio itself will not last long and will not pull the absence of an advertisement in it. Besides the advantages of the radio broadcast is able to reach out to all consumers in the region, including in rural areas, villages, far from the city. In terms of Law No. 32 of 2002 and the terms of Article 1320 KUHPeradata agreement. The purpose of the author of this thesis is to find out how the process of agreement ads in Solo Radio FM, and then to determine the rights and obligations between the radio with the company in advertising, and to determine the legal responsibility if one party breaks or make mistakes in the implementation advertising. This research is a kind of study is a normative legal research method is a method to bring the problem under study effort with the empirical juridical nature of the law. This empirical approach covers the principles of law, legal systematics, synchronization (adjustment) law.